Interstitial cell tumor of the left testicle in a dog - CHEEDE, G S; KANG, R S; GANDOTRA, V K; PRABHAKAR, S; PANGAONKAR, G R; BANGA, H S (The Indian Journal of Animal Reproduction, 2023)
A case of interstitial cell tumor of left testicle of a dog is put on record in the present communication.